The Effect of the Team Game Tournament Cooperative Learning Model on Civic Education Learning Outcomes - I Putu Agistyawangsa; I Made Citra Wibawa; Alexander Hamonangan Simamora (Universitas Pendidikan Ganesha, 2024)
The low student learning outcomes in Civics subjects indicate the need for innovation in the application of learning models that are more interactive and actively involve students. This study aims to examine the effect of using the Team Game Tournament Type Cooperative learning model on the learning outcomes of Civics of grade V students. The method used in this research is experimental research with a quasi-experimental design. The research population used in this study were grade V students consisting of 6 classes in 6 schools. The sampling technique used in this study was Cluster Random Sampling so that each class had the same opportunity to become a research sample. Data collection was carried out using the test method, namely measuring the competence of Civics knowledge. The collected data were analyzed using descriptive statistical analysis and inferential statistical analysis. The results showed that Team Game Tournament (TGT) Cooperative Learning significantly improved learning outcomes and student engagement, as evidenced by the increase in pretest to posttest scores as well as increased student motivation and participation in class. In conclusion, this approach is able to improve student understanding through collaborative, competitive, and fun activities, thus creating a more interactive and effective learning environment. The implementation of TGT can be a significant alternative in improving the quality of learning and the achievement of student learning outcomes in Civics subjects.